Comparative Study of Single and Multiple Pre-treatments of Rice Straw on Cellulose Content for Bioethanol Production - Dewi, Luthfi Kurnia; Miranda, Ni Made Zevika; Rabbani, Hashinatul Fikrial; Nirwana, Wa Ode Cakra (Jurnal Rekayasa Proses, 2024)
Utilization of lignocellulosic biomass for ethanol production has increased. One source of lignocellulosic is rice straw which contains cellulose, hemicellulose, and lignin. Before being used as an ingredient for bioethanol production, it needs to be pre-treated with alkali or acid. One of the factors that affect pre-treatment is the concentration of alkali or acid. The purpose of this study was to determine the concentration of NaOH and H2SO4 in single and multiple pre-treatment which produced the highest cellulose content for bioethanol production. The concentration of NaOH and H2SO4 are 0.75 M; 1 M and 1.5 M. Pre-treatment was carried out at room temperature for 90 minutes. Cellulose, hemicellulose, and lignin content were analyzed using the Chesson Datta method. The variable that produced the highest cellulose was continued to the Simultaneous Saccharification and Fermentation (SSF) at room temperature and analyzed for reducing sugar and bioethanol contents. The results showed that the highest cellulose content of 60.79% was found in single pre-treatment of 0.75 M H2SO4 of 44.89%, 1.5 M NaOH and multiple pretreatments of 0.75 M H2SO4 – 1.5 M NaOH of 68.14%. The highest bioethanol content was obtained in the multiple pretreatments of 0.75 M H2SO4 – 1.5 M NaOH of 23%.